2022-RA-1068-ESGO Canadian practice patterns of primary treatment in advanced (stage III-IV) low grade serous ovarian carcinoma. (20th October 2022) - Brodeur, Melica; Bryce, Maggie; Carey, Mark; Gien, Lilian; Kim, Hannah; Lau, Susie; Lewis, Jordan Adelle; Fernandez, Marta Llaurado; Lytwyn, Alice; Monteiro, Sandra; Scott, Stephanie; St-Onge, Genevieve
Abstract : Introduction/Background: Low grade serous ovarian carcinoma (LGSC) is rare and studies informing evidence-based treatment are lacking. We developed a survey to determine Canadian practice patterns relating to the primary treatment of advanced LGSC. A secondary objective was to explore interest and barriers in participating in a prospective LGSC database. Methodology: Using REDCap software, a descriptive 21-question survey in English and French was designed by the rare cancer Community of Practice/The Society of Gynecologic Oncology of Canada. This was distributed to 126 registered Canadian medical and surgical oncologists. Questions were designed to assess provider characteristics and primary treatment preferences. Results: 80 responses were received from providers across eight provinces for a response rate of 63.5%. 76.3% of providers tailor their treatment approach based on the presence of residual disease following surgery. In this group, the most common regimen was chemotherapy with hormone replacement therapy (HMT) when residual disease was present (38.0%), and HMT only among patients without residual disease (41.0%). Among the 23.7% of providers who do not tailor treatment based on residual disease, surgery, chemotherapy, and HMT is the most common treatment (57.9%). Carboplatin-taxol was the preferred chemotherapy (98.7%), while letrozole was most commonly chosen as HMT (81.6%). Fertility sparing treatment in advanced LGSC was rarely offered (11.8%). 34.2% of respondents referred patients for genetic testing. Most centers did not have active clinical trials for LGSC (86.8%). 90.8% expressed interest in participating in a rare cancer registry. Perceived barriers to participation in a registry included time constraints (50.7%), lack of resources (40.0%) and ethics challenges (29.3%). Conclusion: Among Canadian providers, the approach to treating LGSC varies. Most surveyed physicians support the development of a prospective database to track patient outcomes and optimize treatment recommendations.